System modeling, experimental validation and pressure estimation of the pneumatic braking system. (15th March 2023) - Wei, Lingtao; Wang, Xiangyu; Liu, Haichao; Li, Liang
Abstract: The accessibility and adjustability of the brake system pressure give more control freedom to the vehicle dynamics control. Pneumatic braking system works as the most common form in vehicles, whose overall model is the basis for pressure estimation and control. This paper analyzes the coupling relationship of the relay valve, ABS valve, pipeline and braking cylinder in the pneumatic braking system. The dynamic performances of each component including the electrical, electromagnetic, mechanical and fluid performance are studied. In the fluid modeling, the distributed model is proposed further for describing the behavior of compressible gas in pipelines. Next, the pressure estimation algorithm and the rule-based pressure control strategy are designed based on the proposed model. Finally, the proposed model and strategy is verified in bench and vehicle experiments. The results show that the models are able to represent the behavior of the typical pneumatic braking system, and the pressure estimation and control based on it meets the application needs of real vehicles.